2010
DOI: 10.1038/modpathol.2009.147
|View full text |Cite
|
Sign up to set email alerts
|

Grading of gastric foveolar-type dysplasia in Barrett's esophagus

Abstract: Dysplasia is the gold standard biomarker of cancer risk in Barrett's esophagus, but its diagnosis remains difficult. This is due in part to its multitude of histological appearances. One aspect receiving little attention concerns gastric-type Barrett's dysplasia, which is distinctly different from the well-established intestinal variant. Recognition of gastric-type dysplasia and development of separate grading criteria are required. The prevalence, diagnostic criteria, and natural history of gastric-type Barre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 23 publications
0
42
0
2
Order By: Relevance
“…They stressed on the need for further studies in this regard. 17 Cameron et al stated in their article that esophageal adenocarcinomas occurring in the absence of BE, represent cases, where the metaplastic mucosa has been destroyed by the tumor. 18 To conclude, diagnosing BE is of paramount importance, as it can subsequently develop dysplasia and carcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They stressed on the need for further studies in this regard. 17 Cameron et al stated in their article that esophageal adenocarcinomas occurring in the absence of BE, represent cases, where the metaplastic mucosa has been destroyed by the tumor. 18 To conclude, diagnosing BE is of paramount importance, as it can subsequently develop dysplasia and carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…As per Fenoglio-Preister, dysplasia and carcinoma virtually never develop in any columnar epithelium other than in an intestinal metaplastic one. 2 However, in one of the most recent studies, Mahajan et al 17 showed that even cases with the gastric foveolar type of Barrett's esophagus can undergo dysplastic and carcinomatous transformation. They stressed on the need for further studies in this regard.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8][11][12][13][14][15] Because of its recent description, the gastric variant of Barrett's dysplasia was not separately analyzed in this study. [16][17][18] This omission is unlikely to have affected the reported results; however, because gastric-type Barrett's dysplasia represents a minority of dysplasia cases (B15%). It is also substantially more subtle than intestinal-type dysplasia, leading to under rather than over diagnosis, the subject of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, goblet cells by themselves are not reliable indicators of progression, 13,[92][93][94][95][96] and only certain subtypes show unequivocal association with carcinoma. 52,88,97 As a result, the term paracancerous has been introduced to characterize IM lesions.…”
Section: Discussionmentioning
confidence: 99%